Growth Kinetics Studies of Saccharomyces Cerevisiae for Bioethanol Production of Oil Palm Empty Fruit Bunches - Adrianto Ahmad; Yelmida Yelmida; Lita Darmayanti; Sri Rezeki Muria (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2026)
This study aims to analyze the growth kinetics of saccharomyces cerevisiae in the bioethanol production process based on oil palm empty fruit bunch waste. Growth kinetics parameters are an important basis for fermentor design, especially the maximum growth rate constant to determine the minimum biomass residence time. The minimum biomass residence time is a critical point for fermentor operation in processing empty oil palm fruit bunches into bioethanol. This research was the laboratory experimental research method with a quantitative approach. The result in this research shows the growth kinetics parameters of saccharomyces cerevisiae have been successfully determined to produce the highest bioethanol at 5% KOH variation. Kinetic analysis established a substrate saturation coefficient (KS) of 28.195 g/L under the S < 10 K criterion, alongside a maximum specific growth rate (mM) of 0.00073 hour?¹. Furthermore, the process demonstrated a biomass yield (Yx/S) of 0.053 g/g and a product yield (YP/S) of 2.96 g/g, culminating in a final bioethanol productivity of 0.41 g/L·h. Therefore, these growth kinetics parameters can be used in designing a fermentor system for processing empty oil palm fruit bunches into bioethanol.